The role of fingers in the development of logical-mathematical skills in Early Childhood Education (Edma 0-6: Educación Matemática en la Infancia, 2021)
Different teaching tools have gradually been introduced in mathematical education in order to achieve a significant learning. In this paper, we intend to justify and recommend the use of fingers in preschool classrooms as a didactic tool in the development of children’s logical-mathematical skills and, in particular, in their ability in the start with enumeration and calculus. Fingers appear to be the most natural tool when counting, either to point at the successive elements, or to establish a one-to-one relationship between fingers and objects. Nevertheless, this is not the kind of use to which we refer in this work, but the role of fingers in the subitizing process, for eventually this will generate mental images which will help the children to do basic arithmetic operations promptly and confidently, as well as it has a positive influence on the acquisition of the concept of number. The use of fingers as a tool for mathematical learning does not restrict itself to the field of calculus and enumeration. Thus, some activities of logic and geometry are also included in the didactic proposal.
Keywords: Counting; Subitizing; Fingers; Maths in Early Childhood Education